MEANING MAKING BY A THIRD-GRADE DYSLEXIC STUDENT THROUGH DIGITAL STORYTELLING IN ENGLISH LEARNING - Istiqomah, Wasiatul Fajar; Setyaji, Arso; Wiyaka, Wiyaka (Universitas PGRI Semarang, 2025)
Dyslexia affects approximately 10–20% of the global population, yet it remains widely misunderstood and frequently misidentified by educators. Characterized by difficulties in phonological processing, dyslexia poses significant challenges within traditional, text-heavy English instruction. However, many dyslexic learners exhibit strengths in visual, spatial, and creative domains. This single-case qualitative study investigates how a third-grade student with dyslexia constructed meaning through Digital Storytelling (DST) in the context of English learning. Through two personal and autobiographical digital narratives, the participant employed multimodal tools; including images, narration, and visual sequencing, to convey meaning rooted in lived experience. The findings reveal that DST functioned as a cognitive scaffold, reducing extraneous cognitive load and facilitating expressive, schema-based communication. Her strong preference for realism and visual representation over fictional or abstract content illustrates the principles of Cognitive Load Theory (CLT), Dual Coding Theory, and Multimodal Discourse. This study underscores the pedagogical value of DST as a learner-centered, inclusive approach that leverages dyslexic students’ cognitive strengths to support comprehension, retention, and language development in early English education.